The Sixth Amendment Through the Lens of the Constitutional Moment - Mollov, Stoil (Law Journal of New Bulgarian University, 2024)
The article examines the amendments of the Constitution of Republic of Bulgaria, adopted under the Law on Amendments and Supplements to the Constitution of the Republic of Bulgaria, published in the State Gazette, issue no. 106, dated 22.12.2023, within the context of the complex process of adoption and amendment. The development of the constitutional framework and the practice of institutions such as the caretaker government and the judiciary are discussed in light of the “constitutional moment” concept introduced by American scholar Bruce Ackerman. It pertains to historical junctures necessitating constitutional change due to conflicts or inadequacies in the existing order. The article delineates two primary issues: the limitation of presidential powers during political crises and reform of the judiciary. It restricts the president’s powers in appointing a caretaker government and strengthens parliamentary oversight, which reinforces the parliamentary nature of governance. The second part focuses on issues within the judiciary, emphasizing the need for independence and accountability of the judicial branch and the prosecutor general. The article also examines Constitutional Court Decision No. 13 of July 26, 2024, on Constitutional Case No. 1 of 2024, noting that the sixth amendment represents a partial success in judicial reform while underscoring the need for ongoing efforts to achieve a stable rule-of-law-based and democratic state.